Censuses of breeding birds in a South Norwegian arctic-alpine habitat three decades apart show population declines in the most common species - Byrkjedal, Ingvar; Kålås, John Atle (Ornis Norvegica, 2012)
Breeding bird censuses along line transects on the Hardangervidda plateau, southern Norway, were performed on open mountain heath at about1250 m elevation in 1980 and repeated in 2010 and 2011. Four passerine species and three species of waders constitute the commonest breeders. Significant decrease in numbers was found in the three commonest species, Meadow Pipit Anthus pratensis (down 40 %), Northern Wheatear Oenanthe oenanthe (down 65–67 %) and, in particular, Lapland Bunting Calcarius lapponicus (down 82–87 %). The decline in Lapland Bunting is discussed in relation to changes in the vegetation on the breeding grounds probably caused by reduced grazing and climatic changes, and in relation to possible negative factors in parts of the wintering area.